Determinant Factors of Type 2 Diabetes Mellitus Among Older Adults in Kelating Village - Pake, Indry Agatha Rihi; Putra, I Made Gede Dwipayana; Adrya, Jessica; Jayaningrat, Dewa Ayu Tri; Wirawan, I Made Suma (Syntax Corporation, 2025)
Type 2 diabetes mellitus (DM) increased in the elderly population due to metabolic changes and decreased function of pancreatic β cells. This study aims to determine the prevalence of type 2 diabetes mellitus in the elderly and examine the risk factors—such as age, gender, blood pressure, and uric acid levels—that influence the incidence of type 2 DM. This cross-sectional study involved 31 elderly people (≥60 years) in Segara Santhi, Kelating Village, Tabanan, who were selected using purposive random sampling. Fasting blood glucose and uric acid levels were checked using Accu-Chek after fasting for at least 8 hours. Data analysis used the Fisher's Exact Test with a significance of p<0.05. The results show prevalence of type 2 DM was 64.5% (20 of 31 respondents). Age and type 2 DM had no significant association (p= 0.262). However, there was a significant association between type 2 DM and gender (p = 0.012) and uric acid levels (p = 0.029), but not with blood pressure (p = 1,000). The prevalence of type 2 DM in the elderly in Segara Santhi is quite high, but age is not the main factor. Other factors such as diet, physical activity, and genetic predisposition may play a greater role. Further studies with larger sample sizes and multivariate analysis are needed to understand the risk factors for type 2 DM in the elderly more specifically.